The formal sector wage premium and firm size for self-employed workers - Olivier Bargain; Eliane El Badaoui; Prudence Kwenda; Eric Strobl; Frank Walsh (University College Dublin, UCD School of Economics, 2012)
We develop a model where workers may enter self-employment or search for jobs as employees and where there is heterogeneity across workers' managerial ability. Workers with higher skills will manage larger firms while workers with low managerial ability will run smaller firms and will be in self-employment only when they cannot find a salaried job. For these workers self-employment is a secondary/informal form of employment. The Burdett and Mortensen (1998) equilibrium search model is used for illustration as a special case of our more general framework. Empirical evidence from Mexico is provided and demonstrates that firm size wage effects for employees and selfemployed workers are broadly consistent with the model.
Keywords: J31; O17; 330; Self-employment; Managerial ability; Informal sector